A snapshot of coal-fired power generation in Bangladesh: A demand–supply outlook - Islam, Aminul; Ahmed, Mohammad Tofayal; Mondal, Md. Hossain Alam; Awual, Md. Rabiul; Monir, Minhaj Uddin; Islam, Kamrul (John Wiley & Sons, 2021)
Despite the numerous exemplary efforts taking place to develop sustainable systems of power generation globally, coal will remain an essential and significant part of Bangladeshʼs energy generation. The Government of Bangladesh needs to provide a more reliable and transparent power market for citizens to meet Bangladeshʼs rising energy demand. Consequently, various coal‐based mega projects were undertaken by the Bangladesh government to ensure an affordable and reliable power supply. Half of the targeted electricity was designated to be produced from imported coal. Hence, the development strategy or the reformation of policy in the energy sector may contribute to the current shortcomings in policy approach including inadequate energy infrastructure, regulation and co‐ordination issues. This review focuses on the increasing demand for coal, supply issues, socio‐environmental requirements and significant coal import to encourage realistic advancement of the energy sector in Bangladesh. Moreover, forecasting the requirement of coal for mega power projects from 2021 to 2041 was highlighted. The water resource supply for coal‐based power plants and approaches for reducing CO2 and other emissions were also addressed. Finally, initiatives for fulfilling Sustainable Development Goals in the Bangladesh energy sector were also discussed in this review.